CREDIT SALES MANAGEMENT SYSTEM IN PT ANDALAN SEJAHTERA PEKANBARU (International Journal of Business and Information Technology, 2022)
The Sanjaya shop is a shop that sells various kinds of machines such as pumps, diesel and many more. Sales of their PT Andalan Sejahtera Pekanbaru is one of the companies engaged in the sale of Spare Parts for Heavy Equipment, Machinery, Vehicles and so on. In addition to cash sales, credit sales are also applied. Transaction processing is carried out almost every day. In managing transaction data, especially for credit sales transactions, it is still done manually. Therefore, an application, namely General Ledger, is proposed to facilitate more effective sales transactions. The purpose of this study is to analyze the credit sales management system. The data collection method used was the observation method, by making direct observations on the object of research.